Long-term outcome after percutaneous closure of persistent left superior caval vein draining into the left atrium: a contrast-enhanced CT study. (8th May 2017) - Marini, Davide; Castagno, Matteo; Millesimo, Michele; Ferroni, Francesca; Ferraro, Gaetana; Pace Napoleone, Carlo; Agnoletti, Gabriella
Abstract: Background: Data regarding long-term outcome after percutaneous closure of left superior caval vein draining into the left atrium are lacking. The aim of the present study was to report the long-term follow-up by using contrast-enhanced CT. Methods: In all, three patients underwent percutaneous closure of left superior caval vein draining into the left atrium between 2005 and 2015. All of them were evaluated clinically and underwent contrast-enhanced CT. Results: In one patient, the Amplatzer ® Septal Occluder was used. In two patients, the Amplatzer ® Vascular Plug type-1 was preferred: the device size/LSVC diameter ratio was 1.7 in the child and 1.2 in the adult. There were no early-onset or long-term onset complications. CT was performed 1, 2, and 10 years after the procedure, respectively. Complete occlusion of the vessel was documented in all. After 10 years since the procedure, CT revealed a persistent trivial residual shunt through the accessory hemiazygos vein in one patient, in whom the device was implanted above its drainage into the left superior caval vein. When an Amplatzer ® Vascular Plug type-1 is oversized compared with the venous vessel diameter, it immediately assumes a dog-bone shape that disappears early to regain its shape memory and nominal size. Conclusions: Percutaneous occlusion of left superior caval vein draining into the left atrium has excellent early and long-term outcomes. The optimal implantation of the device is below the drainage of the accessory hemiazygos vein, when present. The device might be oversized compared with the left superior caval vein diameter according to the age of the patient.